2020
DOI: 10.3390/su12219036
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of Institutions in Transformative Contexts: Institutional Change and Conflicts

Abstract: The study of conflicts over natural resources is neither governed by a coherent set of theories nor limited by strict disciplinary boundaries. Rather, it encompasses a multitude of conceptions grounded within a wide array of disciplines and epistemological assumptions concerning the links between institutional change and conflicts, often concluding in contradictory propositions. This article aims at providing conceptual guidance for the special issue, by reviewing institutional research with a particular focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 98 publications
1
12
1
1
Order By: Relevance
“…Each of the first six (6) DPs were measured with a five (5) points Likert scale ranging from 'totally disagree' to 'totally agree' (see Table 3). Following Gari et al [39], who propose a scale from 'absence' (0) to 'present' (1) of the DPs, we coded the answers ranging from 'total disagreement' (0) to 'total agreement' (1). We also considered intermediate answers with 0.25 for 'disagreement', 0.5 for 'neutral', and 0.75 for 'agreement'.…”
Section: Complementary Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of the first six (6) DPs were measured with a five (5) points Likert scale ranging from 'totally disagree' to 'totally agree' (see Table 3). Following Gari et al [39], who propose a scale from 'absence' (0) to 'present' (1) of the DPs, we coded the answers ranging from 'total disagreement' (0) to 'total agreement' (1). We also considered intermediate answers with 0.25 for 'disagreement', 0.5 for 'neutral', and 0.75 for 'agreement'.…”
Section: Complementary Methodsmentioning
confidence: 99%
“…The seminal paper of this special issue: "Revisiting the Role of Institutions in Transformative Contexts: Institutional Change and Conflicts" [1], brings to the discussion this unprecedented setting for humanity and the potential surge of conflicts with a focus on the role of institutional change. The author argues three (3) causes for institutional change: (i) the lack of an institution, (ii) a futile institution, or (iii) the need to adjust the institution given external disturbances (p. 9, [1]). This paper dives into the latter cause for institutional change, where climate change introduces the external disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffee supply is mainly based on exports from countries with different institutional architectures. As the rules of the game and the configuration of the agri-food chains are different in each producing country, contract enforcement, definition of property rights, and external arbitration shall not be the same as well [29,30].…”
Section: Unfair Trade Practices: Differences In Margins Obtained By C...mentioning
confidence: 99%
“…FNC [Federación Nacional de Cafeteros de Colombia] has shown that it is far more expensive to take a container from coffee growing in Armenia to Cartagena (900 km) than from In Brazil, coffee production involves complex governance mechanisms to coordinate the whole chain towards both domestic and international markets [21,40]. Although present in remote locations, the supply chain involves a supportive activity from private agents who collectively handle issues that government fails to address [30,41]. There is no public organization responsible for the sector in the country, but there are several associations and cooperatives that provide support to producers.…”
Section: Institutions and Infrastructurementioning
confidence: 99%